A Robotic Sentry For Korea's Demilitarized Zone. - Kumagai, J. (IEEE spectrum)
This paper presents a new gun-toting sentry robot, developed by Samsung Techwin Co. for the South Korean government. The SGR-AI robot uses a low light camera and pattern recognition software to distinguish humans from animals or other objects and, if necessary, can fire its built-in machine gun - a Daewoo K3. By deploying the robots, the government may be able to significantly reduce the mandatory two years of military service that all young Korean men now serve